The preparation and properties of an alloying modified ceramic-precursor high-temperature resistant adhesive for joining zirconia ceramics and titanium-based superalloys. (December 2022) - Chen, Zhaoli; Liu, Jingxuan; Wu, Yu; Feng, Zhaojie; Li, Jiancun; Feng, Zhenyu; Zhang, Qingsong; Wang, Mingchao
Abstract: To facilitate the joining process for heterogeneous hot end components of zirconia and titanium-based alloy, an alloying modified ceramic-precursor high-temperature resistant adhesive was prepared from epoxy reinforced silicone resin emulsion and various modifiers. The thermal properties, compositional and structural evolution of the adhesive with temperature, as well as the interfacial reactions and diffusion, were comprehensively studied to understand the bonding mechanism. The addition of Si-Al-Ti-Ni metal fillers could effectively change the reaction path in the adhesive in the temperature range of 600–1000 ℃, and promote the formation of multiple intermetallics (Al-Ni, Ni-Si, Ni-Zr, etc.). The chemical reaction also occurred at both two interfaces with the generation of NiZr, ZrSiO4 (ZrO2 /adhesive) and TiSi, Ti5 Si3 (adhesive/TC4). Besides, the oxidation of boron carbide apparently increased the compactness of the bonding layer. Therefore, the bonding strength kept increasing in the temperature range of 600–1000 ℃ and close to 20 MPa at 800–1000 ℃. With the formation of the composite compose`d of multiple ceramics, intermetallics and borosilicate glass, the adhesive showed good thermal stability and oxidation resistance and still provided above 9 MPa after 50 thermal cycles in the range of RT-900 ℃. Graphical Abstract: ga1 Highlights: Si-Al-Ti-Ni fillers promoted intermetallics' formation in the ceramics' transformation stage. Chemical bonding based on the formation of NiZr, ZrSiO4, TiSi, Ti5 Si3 began work at 600 ℃. The adhesive showed good oxidation resistance, and suitable CTE matched with two substrates. The bonding strength was about 20 MPa after sintering at 800–1000 ℃. The bonding strength was still above 9 MPa after 50 thermal cycles in the range of RT-900 ℃.